2012
DOI: 10.3892/or.2012.1981
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of matrix metalloproteinase-9 mRNA by valproic acid plays a role in inhibiting the shedding of MHC class I-related molecules A and B on the surface of human osteosarcoma cells

Abstract: Abstract. Valproic acid, a histone deacetylase inhibitor, increases the expression of cell surface MHC class I-related chain molecules (MICs) A and B (MICA and B) in osteosarcoma cells and decreases their secretion of soluble MICA and MICB, which are produced by the proteolytic cleavage of cell surface MICs. Osteosarcoma cells have been reported to produce high levels of matrix metalloproteinase (MMP)-2 and -9. In this study, we investigated the involvement of MMP-2 and -9 in the inhibitory action of valproic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Soluble TL1AL72-L251 acts mainly in a paracrine manner to influence cells in the immune system, whereas the TL1AV84-L251 fragment acts via the autocrine pathway to induce the inhibition of the proliferation and apoptosis of endothelial cells (31). Our previous report indicated that VPA-treated OS cells do not exhibit increased ADAM17 gene transcription (32). Hence, the increase in the expression of soluble VEGI induced by HDAC inhibitors may involve a different mechanism of action than that mediating the shedding of membrane-bound VEGI.…”
Section: Discussionmentioning
confidence: 96%
“…Soluble TL1AL72-L251 acts mainly in a paracrine manner to influence cells in the immune system, whereas the TL1AV84-L251 fragment acts via the autocrine pathway to induce the inhibition of the proliferation and apoptosis of endothelial cells (31). Our previous report indicated that VPA-treated OS cells do not exhibit increased ADAM17 gene transcription (32). Hence, the increase in the expression of soluble VEGI induced by HDAC inhibitors may involve a different mechanism of action than that mediating the shedding of membrane-bound VEGI.…”
Section: Discussionmentioning
confidence: 96%
“…Valproate treatment in osteosarcoma cells downregulates MMP9 expression and thereby enhances the expression of MICA and MICB ligands on the cell surface while downregulating the release of soluble forms of these ligands 79 . Moreover, the hypomethylating reagent hydralazine reduces the release of soluble form of MICA and MICB in conjunction with enhanced surface expression of these ligands 80 .…”
Section: Mechanisms Involved In the Secretion Of Snkg2dlmentioning
confidence: 99%
“…Our data collectively indicate that the release of sMICA is associated with tumor progression and metastasis in RCC. Shedding of NKG2D ligands, in particular MICA, from the cell surface represents a mechanism by which tumors escape NKG2D-mediated immunosurveillance (Kohga et al, 2012;Yamanegi et al, 2012). The production of sMICA has been found to impair NKG2D expression and NK cytotoxicity (Raffaghello et al, 2004).…”
Section: Discussionmentioning
confidence: 99%